Performance assessment of portable raman spectroscopy for analysis of ecstasy tablets - Hiang, Ng Choon (2024)
Ecstasy tablet, a type of street drug originally consists of 3,4-methylenedioxymethamphetamine (MDMA), provides stimulant and hallucinogen psychoactive effects. They are frequently found in night clubs, musical festivals, or other recreational events believed to create relaxing experience for the users. From the forensic perspective, when the drug of abuse is suspected in such scenarios, the law enforcement personnel would then require an easy-to-perform, quick and accurate method to detect the existence of such controlled substance prior to seizure and subsequent forensic examination. In this study, the performance of a portable Raman spectroscopy was assessed as the primary aid in determining ecstasy tablets at the point of use. A total of 130 ecstasy tablet samples were physically examined. Subsequently, they were analysed by Raman spectroscopy and characterised by gas chromatography-mass spectrometry (GC-MS). The performance of Raman spectroscopy was further assessed in terms of its accuracy, sensitivity, and specificity corresponding to the GC-MS results. From the study, the physical examination showed that the ecstasy tablet appeared in various design and colour. MDMA dominated the composition of ecstasy tablets obtained from case samples in this study. Portable Raman spectroscopy showed an accuracy of 85.4% in analysing the ecstasy tablets, while the sensitivity and specificity were determined as 85.2% and 100%, respectively. No false positive of MDMA or other drug were reported. For drug profiling, the hierarchical cluster analysis (HCA) had formed eight major cluster of ecstasy tablets. The combination of GC-MS and Raman spectroscopy results allowed for the discrimination of tablet samples up to 41 groups. To conclude, portable Raman spectroscopy is a suitable technique for targeted determination of the presence of ecstasy tablets, especially in forensic cases that require technique, which is portable, non-destructive, rapid, and allows for mass screening during on-site testing by the law enforcement personnel.